Analysis of Factors Affecting the Low Participation of Universitas Negeri Padang Students in Joining Students’ Organization Activities - Hijriyantomi Suyuthie; Feri Ferdian; Waryono Waryono (Postgraduate School, Universitas Negeri Padang, 2019)
The purpose of this study to analyze the determinant factors affecting low Universitas Negeri Padang students’ participation in the activities of students’ organizations. This type of research was explanatory research. The sampling technique is done by purposive sampling. The technique of data collection was through questionnaires. The research population for the data quantitative in this study was Universitas Negeri Padang students of S1, D4 and D3 programs registered actively in the semester of July December 2018 which were in 3rd (third), 5th (fifth) and 7th (seventh) semester with a total of 24,395. The number of samples is 580 people with a margin of error of 20%. Quantitative data analysis techniques used factor analysis and descriptive analysis. The results of this study show that of the 19 indicators analyzed using factor analysis to determine the factors that influence the low student participation in student organizations activities, there are 3 factors, namely willingness and ability factors with eigenvalue 8,080, opportunity, program and environment factors with eigenvalue 1,611, and social factors with eigenvalue 1,322.